NOTAS SOBRE EL PRIMER CRÁNEO DE RlOJASAURUS INCERTUS (DINOSAURIA, PROSAUROPODA, MELANOROSAURIDAE) DEL TRIÁSICO SUPERIOR DE LA RIOJA, ARGENTINA (Ameghiniana, 2014)
An almost complete skull and jaws of Riojasaurus incertus demonstrates that the melanorosaurid skull is the most primitive among prosauropod dinosaurs. The preorbital depression and opening are large, placed anterior to a vertical lacrimal; the jaw articulation is in line with the alveolar plane of the maxilla; the basicranial region does not show a step between the basioccipital and the basisphenoid; and the teeth are rather conical , not leaf shaped. The position of the lacrimal and the preorbital depression suggests that sauropods may be derived from Melanorosauridae and not from prosauropods with a backwardly inclined lacrimal and a preorbital opening that is placed partially below it. The origin of the Prosauropoda is briefly discussed and some shared derived characters between Riojasaurus and Coelophysis appear consistent with the assumption that Triassic Ceratosauria and Melanorosauridae possibly had a near common ancestor, -not Herrarasauridae-, from which both evolutionary lines split.